Modeling the Consequences Release of Cyanogen agents in Bushehr Nuclear Power Plant Neighborhood Using PHAST, ALOHA and WISER Software - rasoul khorram (Salāmat-i kār-i Īrān, 2020)
Background and purpose Many efforts have been made to use chemical components as weapons throughout history until the Germans first employed chlorine gas cylinders in April 1915 at Ypres Belgium against French and Canadian soldiers. Leaving 5,000 dead and 15,000 injured, it was the first practical application of chemical agents. The Geneva Protocol in June 1925, which was an attempt to prevent the use of chemical agents in the war, was not very successful and since 1945, chemical weapons have been utilized frequently in wars. One of the most substantial cases in this regard ocurred during the war that Iraq imposed on Iran. The toxic gases employed in the killings were reported to be of three types including Mustard gas, nerve gas, and cyanide gas; the latter killed many Halabja residents. Because as soon as it is inhaled (2 or 3 respirations), it can cause the bloodchr('39')s capability to absorb oxygen, which gradually spoils the blood, causing overall toxicity in the body. That is why these compounds are named blood agents in the military. These compounds consist of Hydrogen Cyanide (AC), Cyanogen Chloride (CK) and Cyanogen Bromide (CB). Failing to take proper defensive measures after the emission of these gases can irreversibly damage the health of the affected citizens. The current study reviewed the scenario of releasing cyanogen agents on the population of the suburbs of the Bushehr Nuclear Power Plant in chemical attacks, whose results can be utilized in the emergency response program. The methodology of the Study After analyzing the spectral properties of chemicals known as combat gases by various sources such as database software, Persian and English websites and copious books, the cyanogen group, including cyanogen chloride and cyanogen bromide, were chosen from amongst the mentioned compounds due to releasing the extremely flammable and toxic cyanide ions and hydrogen cyanide. Then, their toxicity effects were modeled and determined by Emergency Response Planning Guides (ERPGs) and Alternative Criteria (STEL, IDLH) for both high- and low-density combustible materials through Baker method using PHAST, ALOHA, and WISER software. Findings The investigation of the effect of AC gas vapor diffusion revealed that these vapors created clouds over a range of 15 to 133 m from the diffusion point (flammability range). If the cloud exploded in low-density environments as a result of firing a gun or electric spark, a hot flash pressure would be formed, the impact wave of which could dealt with severe structural damages, including the skewing of buildings over a radius of 2449.7 m. In this situation, deaths caused by direct and indirect injuries due to the exposure to the pressure for up to 40 m were below 1% and 25%, respectively. If the explosion occurred in high-density environments, it would produce a detonation explosion that could create a shock tilting the still structure of buildings up to a radius of 2028 meters. In this case, the death resulting from direct and indirect damages caused by exposure to pressure up to 84 meters, would be 100%. Consequently, as the distance increased, the pressure would decrease to the amount that at a distance of 334 m, the pressure (0.1 to 0.8 bar) would cause the tearing of the eardrum of the exposed persons by 1 to 90%. Modeling results of AC emission proved that the equivalent toxic dose based on ERPG-3 was at 3267 m distance downwind. Everyone at this distance could be exposed to AC gas for an hour without being affected by harm preventing them from taking safety measures, such as wearing individual protective equipment. Modeling the results of cyanogen chloride (CK) and cyanogen bromide (CB) emission revealed that CK in the orange threat zone (0.05 ppm) would extend by 10 km based on ERPG-2 criterion, and red threat zone (4 ppm) would extend up by 7.8 km downwind based on ERPG-3 criterion. In the stable D class, the orange threat zone would increase by more than 10 km and the red threat zone would increase by 5.4 km downwind. Moreover, in the event of a cyanogen bromide leak, the immediate response to isolate the leakage or leakage area in all directions was at least 50 m (150 feet) for liquids and 25 m (75 feet) for solids. The results of AC gas toxicity emission modeling using PHAST software based on alternative criteria revealed that concentration values based on alternative indices (IDLH and STEL) for distances close to the site of chemical spillage (bomb explosion containing AC gas) remained constant over the 900 to 1800 s period. Given the modeling of the instantaneous emission scenario, it is reasonable for the concentration values to be constant over time. The reason behind was that a large portion of the material was released into the surrounding environment in a short period, and its dilution happened slowly. Comparison of the Detonation Explosion Results Using the Baker Computation Model For the nearest (Halileh) and the farthest (harbor) locations, at 424 and 1382 m distances, respectively, from the power plant, it was confirmed that damage caused by explosion at distances close to the power plant, where constructions still happen, resulted in direct death of 10 to 50%, and indirect death of 25% to 50% of the individuals. Whereas, the blast impact was reduced to 154.6 ns / m2, equal to 0.02 Bar, for farther distances. As a result, at distances away from the power plant, detonation explosions, such as hot flashes, would not lead to any serious damages to buildings or individuals because of reduced flame speed and wave density. Comparison of the Modeling Results of CK and AC Gas emission against time revealed that The village of Helileh faced the greatest risk. Because at the initial stages of chemical spillage, both software reported relatively close results in reaching substantial CK and AC densities within a short period. According to the criteria used for evaluating the toxic effects, based on the ERPG-2 criterion, which indicated a rather low maximum allowable level for one hour of exposure to other gases, only 2 or 3 inhalations of these agents are enough to kill a human. Moreover, the concentration results, according to the IDLH and STEL (Alternative criteria) at distances near the chemical spillage spot, the necessity of quick response, particularly for areas close to the gas release center was highlighted. It can be concluded that the scheduling regarding taking defensive measures afforded by PHAST was more rational than that of ALOHA. Comparing the results collected through the ALOHA and PHAST software based on the outcome evaluation criteria of the toxic impacts revealed that in high F / D atmospheric conditions (ERPG-3) the PHAST software provided relatively close results. While for lower concentrations (ERPG-2) with comparable atmospheric conditions, ALOHA also submitted very similar outcomes. Accordingly, a comparison of the results based on the Emergency Response Planning Guidelines criteria suggested that the PHAST software yielded more valid results than ALOHA over longer distances at a stable (F) and relatively stable (D) atmospheric conditions; that is, PHAST software was more capable of delivering accurate results at lower concentrations than ALOHA software. Comparing WISER with ALOHA and PHAST models based on computational speed unveiled that modeling using ALOHA and PHAST software necessitates correct information such as the release type, ambient temperature, humidity, wind velocity, and degree of stability. The above steps are suitable for outcome evaluation in places where the likelihood of an incident is predicted. But for other events, owing to the time insufficiency to obtain the mentioned information and the need for quick reaction, WISER would provide information regarding the protection period, which is within the first 30 minutes of chemical spillage, quickly and easily on mobile devices, tablets, and mobile communication terminals online and offline. Conclusion The results of the current research regarding a 10-ton AC vapor cloud explosion indicated that the distance of 3768 m from the power plant can be regarded as safe from the intrinsic hazard of flammable vapor cloud explosion (VCE), regardless of the type of flammable material _ considering the mass of 4 g defined for AC explosion and its maximum flammability, which also covers the risk range of VCE incident scenarios with fewer volumes and flammability _ to the environment. Furthermore, considering the permitted exposure limits to CK and AC gases based on the results achieved in the current study, and the inadequacy of ALOHA software to the present results at low concentrations (ERPG-2), it was recommended that the farthest distance obtained using the PHAST software and the ERPG-2 criterion, which is determined based on not dealing serious or irreversible damages, should be considered in emergency planning. The limitation of the present study can be attributed to the shortage of access to information on vital (critical and delicate) sites because of their confidentiality. It is, consequently, necessary for the proper experts to examine the effects of the pressure wave and impact of the explosion of various volumes of combat gases on the actual resistance of buildings in those sites to eventually reach the required preparations to deal with possible emergencies in advance.